TUJUAN DAN MATERI PENDIDIKAN ANAK USIA DINI DALAM PERSPEKTIF HADIS - Elvis Winda; Nepi Apriana; Suryani Suryani (Sekolah Pasca Sarjana IAIN Bengkulu, 2022)
Abstract.Early childhood education is described as an important period in child development. Children are born in a state of weakness and helplessness and do not know anything, but they are born in a state of fitrah, that is, pure and clean from all kinds of bad things. Therefore, to maintain and develop the nature that exists in children, parents and educators are obliged to provide positive upbringing to children. Early childhood education in the perspective of hadith aims to instill Islamic values in children from an early age, so that children become Muslim people who are kāffah, who believe and fear Allah SWT. The material for early childhood education in the perspective of hadith is in the form of material for the hadith of deeds such as tauhid education, worship education and moral education.Key words: Early childhood; Education; Hadith Perspective.Abstrak Pendidikan anak usia dini digambarkan sebagai periode penting dalam perkembangan anak. Anak lahir dalam keadaan lemah tak berdaya serta tidak mengetahui apa-apa, tetapi ia lahir dalam keadaan fitrah, yakni suci dan bersih dari segala macam keburukan. Karenanya untuk memelihara sekaligus mengembangkan fitrah yang ada pada anak, orang tua dan pendidik berkewajiban memberikan didikan positif kepada anak. Pendidikan anak usia dini dalam perspektif hadis bertujuan untuk menanamkan nilai-nilai keislaman kepada anak sejak dini, sehingga anak menjadi manusia muslim yang kāffah, yang beriman dan bertaqwa kepada Allah SWT. Materi pendidikan anak usia dini dalam perspektif hadis berupa materi Hadis perbuatan seperti pendidikan tauhid, pendidikan ibadah dan pendidikan akhlak. Kata kunci: Anak Usia Dini; Pendidikan; Perspektif Hadis.